RUNX1a enhances hematopoietic lineage commitment from human embryonic stem cells and inducible pluripotent stem cells - Ran, Dan (American Society of Hematology, 2013)
Advancements in human pluripotent stem cell (hPSC) research have potential to revolutionize therapeutic transplantation. It has been demonstrated that transcription factors may play key roles in regulating maintenance, expansion, and differentiation of hPSCs. In addition to its regulatory functions in hematopoiesis and blood-related disorders, the transcription factor RUNX1 is also required for the formation of definitive blood stem cells. In this study, we demonstrated that expression of endogenous RUNX1a, an isoform of RUNX1, parallels with lineage commitment and hematopoietic emergence from hPSCs, including both human embryonic stem cells and inducible pluripotent stem cells. In a defined hematopoietic differentiation system, ectopic expression of RUNX1a facilitates emergence of hematopoietic progenitor cells (HPCs) and positively regulates expression of mesoderm and hematopoietic differentiation-related factors, including Brachyury, KDR, SCL, GATA2, and PU.1. HPCs derived from RUNX1a hPSCs show enhanced expansion ability, and the ex vivo–expanded cells are capable of differentiating into multiple lineages. Expression of RUNX1a in embryoid bodies (EBs) promotes definitive hematopoiesis that generates erythrocytes with β-globin production. Moreover, HPCs generated from RUNX1a EBs possess ≥9-week repopulation ability and show multilineage hematopoietic reconstitution in vivo. Together, our results suggest that RUNX1a facilitates the process of producing therapeutic HPCs from hPSCs.